2019
DOI: 10.1021/acs.jmedchem.9b00178
|View full text |Cite
|
Sign up to set email alerts
|

Fragment-Based Discovery of an Apolipoprotein E4 (apoE4) Stabilizer

Abstract: Apolipoprotein E is a 299-residue lipid carrier protein produced in both the liver and the brain. The protein has three major isoforms denoted apoE2, apoE3, and apoE4 which differ at positions 112 and 158 and which occur at different frequencies in the human population. Genome-wide association studies indicate that the possession of two apoE4 alleles is a strong genetic risk factor for late-onset Alzheimer’s disease (LOAD). In an attempt to identify a small molecule stabilizer of apoE4 function that may have u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 38 publications
0
47
0
Order By: Relevance
“…Stabilizers: A study on NMR-based fragment screening and various other biophysical methods on APOE4 reported potential stabilizers [10], based on which, substructure search was performed. Similar structures containing stabilizers as their substructures were searched in the PubChem Database (https://pubchem.ncbi.nlm.nih.gov/) and identified total of 77 compounds.…”
Section: Selection Of Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stabilizers: A study on NMR-based fragment screening and various other biophysical methods on APOE4 reported potential stabilizers [10], based on which, substructure search was performed. Similar structures containing stabilizers as their substructures were searched in the PubChem Database (https://pubchem.ncbi.nlm.nih.gov/) and identified total of 77 compounds.…”
Section: Selection Of Ligandsmentioning
confidence: 99%
“…Apolipoprotein (APOE) encoded by APOE gene, is a plasma glycoprotein of 34.15 kDa with 299-amino acids [9] where the receptor-binding region lies in the N-terminal domain (1-164 residues) targeted for fragment-based drug discovery; the C-terminal domain that contains the lipidbinding function runs from 165-299 residues [10,11]. APOE is associated with HDL, very low-density lipoprotein (VLDL), and majorly with chylomicrons [12,13] that regulate lipoprotein metabolism and control the transport and redistribution of lipids among tissues and cells through receptor-mediated pathways [4,11].…”
Section: Introductionmentioning
confidence: 99%
“…The location of the APOE4 interaction surface is indicated by the black curved line encompassing R47 in wild-type TREM2. The APOE4 structures (residues 19-317) depicted are models constructed using X-ray crystallography structures of APOE4 and APOA-I, for the soluble and lipidated forms respectively (PDB IDs: 6NCO (Petros et al 2019) and 3R2P (Mei and Atkinson 2011) and α2-6 linked sialic acids; these can be components of a variety of ligands for example glycan chains on the cell surface, glycosylated proteins, gangliosides, and amyloid plaques (Chatila and Bradshaw 2021;Duan and Paulson 2020;Miles et al 2019). In the context of microglia and AD, the most relevant binding partners for CD33 have yet to be identified.…”
Section: Cd33mentioning
confidence: 99%
“…A study on NMR-based fragment screening and various other biophysical methods on APOE4 reported potential stabilizers (Petros et al, 2019), based on which, substructure search was performed. Similar structures containing stabilizers as their substructures were searched in the PubChem Database (https://pubchem.ncbi.nlm.nih.gov/) and identified total of 77 compounds.…”
Section: Selection Of Ligands Stabilizersmentioning
confidence: 99%
“…Apolipoprotein (APOE) encoded by APOE gene, is a plasma glycoprotein of 34.15 kDa with 299-amino acids (Frieden & Garai, 2012) where the receptor-binding region lies in the Nterminal domain (1-164 residues) targeted for fragment-based drug discovery; the C-terminal domain that contains the lipid-binding function runs from 165-299 residues (Petros et al, 2019;Weisgraber, 1994). APOE is associated with HDL, very low density lipoprotein (VLDL), and majorly with chylomicrons (Singh et al, 2006;Frieden et al, 2017) that regulate lipoprotein metabolism and control the transport and redistribution of lipids among tissues and cells through receptor-mediated pathways (Weisgraber, 1994;Freeman, 2006).…”
Section: Introductionmentioning
confidence: 99%